Developing world communications (London : Grosvenor Press International, 1986)
This study looks at the different types of networks and the aspects of their physical structure, through feasibility study and financing, to reviewing the activities of telecommunications administrations in Europe and the USA.
II 14/01/2019 ; ne 05/07/2019
Loans
Keywords: Telecommunication systems; Telecommunication